Effects of catalysts on emissions of pollutants from combustion processes of liquid fuels = Wpływ katalizatorów na emisję zanieczyszczeń z procesów spalania paliw ciekłych - Bok, Agnieszka; Guziałowska-Tic, Joanna; Tic, Wilhelm Jan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The dynamic growth of the use of non-renewable fuels for energy purposes results in demand for catalysts to improve their combustion process. The paper describes catalysts used mainly in the processes of combustion of motor fuels and fuel oils. These catalysts make it possible to raise the efficiency of oxidation processes simultanously reducing the emission of pollutants.
Keywords: zanieczyszczenia powietrza; ochrona środowiska; emisja zanieczyszczeń; katalizator; pyły; sadza; air pollution; environmental protection; emission of pollutants; metallic catalyst; particulate matter; soot